Paradigm and method in Plato’s Statesman - Speliotis, Evanthia (Revista Archai, 2025)
The Statesman is unique in the particular emphasis it places on paradigm: crafting and presenting two distinct paradigms, in great detail and at some length, but also turning to define and explain paradigm itself as a method that can help us progress from what is familiar to us from perception and experience, to what is unfamiliar and may “exist” only in the realm of ideas and thinking. In this paper I wish first to examine the Stranger’s explanation of paradigm, to see what it is and how it functions. Then, I wish to examine in turn the two paradigms the Stranger offers, the myth and the account of weaving: to see whether and how they fit his explanation of what a paradigm is; to explore how the Stranger employs each in his search for the being and the definition of the statesman; and to consider what each paradigm helps disclose that we might not have as easily discovered without them. The final question will be: what does the Statesman’s highlighting of the being and use of paradigm have to teach us about how we might advance toward knowledge of “the greater things.”